Exploring the interactions between renewable energy, economic growth, agriculture and urbanization in the Mercosur trade-bloc countries - Poveda, Yormy Eliana; Koengkan, Matheus; Fuinhas, José Alberto (Revista Valore, 2021)
The interactions between renewable energy, economic growth, agricultural sector, and urbanization were analyzed for the Mercosur trade-bloc countries over the period from 1980 to 2014. The analysis was performed recurring to panel vector autoregression to capture the rich connections (endogeneity) between the variables over a long period. The results support the existence of endogeneity between variables as well as the presence of a bi-directional causality, between consumption of renewable energy, urbanization, agriculture production, and economic growth, and unidirectional causality from urbanization to agriculture production.